The Role of Reflection and Self-Analysis in Developing Students’ Presentation Skills - Halimatussya’diyah, Siti (Yayasan Nurul Iman Muara Gading Mas, 2024)
This research endeavors to investigate the impact of reflection and self-analysis on the cultivation of academic presentation skills among students enrolled in Indonesian language study programs. Pedagogical approaches integrating reflection and self-analysis are integrated into the curriculum to enhance students’ presentation competencies. Data were gathered through self-reflection forms and presentation performance assessments from a cohort of 110 students before and after the intervention. The findings evince a notable enhancement in students' presentation skills subsequent to the intervention, characterized by a discernible augmentation in self-confidence, proficiency in presentation structuring, and adeptness in addressing queries. The ensuing discourse on the interpretation of the results underscores the pivotal role of reflection and self-analysis in fostering presentation skills development, while also delineating a research lacuna pertaining to comprehending this role within an intercultural context. These findings yield pragmatic implications for facilitating comprehensive and enduring learning outcomes for students within higher education environments.